2020
DOI: 10.32783/csid-jid.v3i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Speed Limiting Using Speed Cameras: Case Study in Indonesian Toll Road

Abstract: Indonesian Police attempt to reduce the fatality rate of traffic accidents by enforcing the law on speed restrictions using speed cameras. The National Police Traffic Corps (Korlantas), from 2017 to 2018, had installed 75 units of speed cameras along Jakarta Toll Roads including Cikampek, Jagorawi, Bitung, and many others. By the end of 2020, Korlantas is expected to install 75 more units on the arterial roads of Jakarta. This study aims to analyze the implementation of vehicle speed deceleration through signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Indonesia has started to introduce AI technology for monitoring speeding behaviour on several toll and urban roads. Patriot et al's case study looking at Indonesian Toll roads found that after the installation of 75 speed camera units, drivers who obeyed the speed limit rose significantly to around 76.6% (45). Furthermore, numerous studies around the world have found the effectiveness of speed camera increases the level of compliance with speed limits resulting in reducing fatality rates.…”
Section: Best Practice For Increasing Speed and Helmet Law Enforcemen...mentioning
confidence: 99%
“…Indonesia has started to introduce AI technology for monitoring speeding behaviour on several toll and urban roads. Patriot et al's case study looking at Indonesian Toll roads found that after the installation of 75 speed camera units, drivers who obeyed the speed limit rose significantly to around 76.6% (45). Furthermore, numerous studies around the world have found the effectiveness of speed camera increases the level of compliance with speed limits resulting in reducing fatality rates.…”
Section: Best Practice For Increasing Speed and Helmet Law Enforcemen...mentioning
confidence: 99%